Penggunaan Bahasa Arab Dalam Penyelesaian Permasalahan Hukum Keluarga Islam Di Indonesia - Muhammad Nur Haris Asyrofi (STAI Hidayatut Thullab Kediri, 2025)
Islamic family law is one of the important fields of study in Islam that regulates various aspects of family life, such as marriage, divorce, child custody, and inheritance. In the Indonesian context, Islamic family law has a significant role in Muslim society, both in the personal and public spheres. Arabic, as the primary source language of Islamic law, plays a fundamental role in understanding and applying Islamic family law. This study aims to examine the use of Arabic in solving Islamic family law problems in Indonesia. This study uses a qualitative research type with a case study approach. The data collection techniques used include interviews, observations, and document analysis. The results of the study show that Arabic plays an important role in the Islamic family justice process in Indonesia. Arabic is used in various stages of the judicial process, ranging from the examination of witnesses, the reading of Islamic legal postulates, to the preparation of court decisions. Good Arabic language skills for Islamic family law practitioners enable them to understand Islamic law in depth, communicate effectively with the parties involved in the case, and produce fair and appropriate court decisions. Although Arabic has an important role in Islamic family law, there are still some challenges in the use of Arabic in the context of Islamic family law in Indonesia. These challenges include the lack of adequate Arabic proficiency among Islamic family law practitioners, limited access to reliable and easy-to-understand Arabic sources of Islamic law, and lack of government attention in the development of Arabic education for Islamic family law. Efforts to increase the effectiveness of the use of Arabic in resolving Islamic family law problems in Indonesia need to be carried out on an ongoing basis. These efforts include improving the quality of Arabic language education for Islamic family law, providing easy access to reliable sources of Islamic law in Arabic, and encouraging the government to pay more attention to the development of Arabic education for Islamic family law